2018
DOI: 10.3928/24748307-20181025-01
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy and Knowledge of Chronic Diseases in Nepal

Abstract: Background: Understanding of risk factors and developing healthy lifestyles is a way of tackling the surging burden of chronic diseases in low-to-middle income countries such as Nepal. Health literacy (HL) has a pivotal role in prevention, adherence to treatment, self-care, and better use of health care; therefore, factors associated with HL need to be studied in the context of Nepal. Objective: This study was conducted to assess the level of HL and explore disease-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 24 publications
2
25
1
1
Order By: Relevance
“…In this community-based study, we identified that being uneducated, with a low level of family income (β = − 5.22, p = .002), and having one co-morbidity were all significantly associated with SMPs among the multi-morbid COPD patients of Nepal. Our finding is consistent with observations from a previous Nepalese study that concluded lack of education among the COPD patients contributed to poor SMPs such as incorrect use of inhalers [5], knowledge on self-care [6] and knowledge on COPD [7]. Patients with no education have poor functional health literacy and thus are more likely to have a poorer understanding of self-management skills including information management, symptoms management, daily lifestyle management, emotional management, and selfefficacy, in turn resulting in poor SMPs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this community-based study, we identified that being uneducated, with a low level of family income (β = − 5.22, p = .002), and having one co-morbidity were all significantly associated with SMPs among the multi-morbid COPD patients of Nepal. Our finding is consistent with observations from a previous Nepalese study that concluded lack of education among the COPD patients contributed to poor SMPs such as incorrect use of inhalers [5], knowledge on self-care [6] and knowledge on COPD [7]. Patients with no education have poor functional health literacy and thus are more likely to have a poorer understanding of self-management skills including information management, symptoms management, daily lifestyle management, emotional management, and selfefficacy, in turn resulting in poor SMPs.…”
Section: Discussionsupporting
confidence: 92%
“…COPD self-management primarily involves self-recognition and management of symptoms, taking medication, having a healthy diet, coping with breathlessness, quitting smoking and engaging in regular physical exercise to maintain good health [4]. Evidence shows that various factors such as educational status [5][6][7], family history of COPD [6], lack of social support [8] and low socioeconomic status of family [9] are associated with poor SMPs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, an approach that is gender based may be required to improve patient health literacy. Another study from Nepal supports our finding that being female was associated with poor health literacy [18,50]. In contrast, evidence from China did not find a relationship between gender and HL while a study from the US, showed females had higher HL, possible due the difference in socio-demographic profiles of the studied populations [11,51].…”
Section: Plos Onesupporting
confidence: 64%
“…A recently published study from Nepal conducted among chronic disease patients recruited from tertiary level hospital and a community hospital using Europe-Asia Health Literacy Survey Questionnaire showed 19% had marginal HL and 54% had inadequate HL [18]. Overall, a higher proportion of patients had low literacy in our study population when compared with studies from India [35] and Bangladesh [36].…”
Section: Plos Onecontrasting
confidence: 42%
“…While Nepal still faces a burden of infectious diseases struggling with inadequate basic hygiene and sanitation along with deep rooted cultural beliefs, the burden of non-communicable diseases is also on the rise [18, 19]. Limited research has been found mentioning health literacy in Nepal [2022] and level of health literacy of the people of Nepal is not known.…”
Section: Introductionmentioning
confidence: 99%